Perception and trends in assessment of students’ learning in physics courses - Tadele, Kumneger; Sitotaw, Belay (Penerbit Universiti Kebangsaan Malaysia, 2018)
The decline in education quality, as it is measured based on the objectives and goals it intended to achieve which are set by the experts and policy makers, becomes a global challenge. Among the many factors that influence the education quality, assessment technique usually takes the front line. This study investigates the teachers’ perception and trends on different assessment techniques used to evaluate students’ learning in physics courses. It also examines the students’ perception towards different types of assessment techniques and questions. Systematic comparison of students’ result scored for different types of questions in some assessments has also been employed to examine their achievement. In addition to administering systematically developed questionnaires which involves both students and teachers, a close and careful investigation of students’ result scored for different courses has been done. Comparative, descriptive and quantitative methods have been used to present the obtained data. The study reveals that almost all physics teachers involved in this study are well aware of different assessment techniques and question types, however, only one or few types of assessment techniques and question types (mainly workout problems) are being used in most of the assessments in physics courses. Most assessments in physics courses are not in line with the pedagogical science principles and can only measure the lower thinking skill of Bloom’s taxonomy structure. Negligence and lack of experience, to some extent, are believed to hamper the efficacy of assessment in improving education quality.